Exploring the Interior Spaces of Music - Boland, Neil (Elsevier, 2026)
This article explores interiority as a spatial phenomenon in relation to music and spatial experience. While physical spaces are accessible to many, interiority remains a uniquely personal domain; it can also contain an intangible yet real experience of space. This interior landscape exhibits characteristics of physical space: it can be vast or enclosed, illuminated or dark, in constant movement or still. While interiority has been examined across disciplines, its explicitly spatial dimensions receive little attention in contemporary academic discourse. Focusing on the spatial perception of a musical interval, this study employs an experimental-experiential methodology to document the researcher's engagement with inner spatial phenomena. Doing this requires deprivatising personal experiences, challenging and disobeying conventional academic paradigms that prioritise external, material phenomena. The article proposes that spatial experience forms a continuum linking bodily, aesthetic and supersensible dimensions of perception. Recognising this continuum invites more porous borders between disciplines and a re-examination of the epistemic conventions that separate art, consciousness and the study of space. By acknowledging interiority as a legitimate site of inquiry, it points toward a broader understanding of a continuum of perception, extending from sensory awareness to supersensible experience and questions the boundaries of what can be known.
Keywords: 1601 Anthropology; 1608 Sociology; 2002 Cultural Studies; 4406 Human geography; 4410 Sociology; 4702 Cultural studies; Inner space; Interiority; Spirituality; Music; Meditation